Education is Translation: A Translation Report - Wu, Lin; Pan, Mengting (Journal of Educational Research and Policies, 2025)
The book Education is Translation: A Metaphor for Change in Learning and Teaching redefines the connotations of teaching and learning from an interdisciplinary perspective, regarding education as a dynamic “translation” process. An English-Chinese translation project of it was conducted to help Chinese readers to gain valuable insights for educational practice in promoting effective communication and interaction between teachers and students, and further driving the improvement and innovation of teaching methods. The Skopos Theory was applied as the theoretical guidance for this translation practice to ensure the accuracy and readability of the target text. It was found that the three rules of Skopos Theory, i.e. the Skopos rule, the coherence rule, and the fidelity rule, were applicable to addressing the difficulties encountered during the translation process. Guided by the Skopos rule, the core objective of translation was set as serving the comprehension needs of target readers. With respect to the coherence rule, conversion method, amplification technique, and sentence structure adjustment were applied to ensure readability of the target text. Based on the fidelity rule, techniques such as literal translation, amplification, and free translation were used to pursue faithfulness of the target text.